Diet and ecosystem services of insectivorous bats assessed with stable isotopes - Assis, Cecília Kruszynski de (2016)
Ecosystem services are natural environmental functions and ecological process that humans benefit from. In the present study, it was highlighted one of the services provided by bats: agricultural pest control. In Brazil, studies with insectivorous bats as potential pest suppressors are still scarce, despite the country being one of the biggest agricultural producers in the world and concentrating a high diversity of those animals. The use of heterogeneous landscapes, formed by native vegetation and crop fields, optimize the investment applied in this search. For that, it was described, for the first time, the bat assemblage in heterogeneous landscape in Piracicaba, at the campus \"Luiz de Queiroz\" that comprehends urbanized and agricultural areas, which provides many food resources for bats. Further, it was tested if there is difference in isotopic values (?13C and ?15N) between bat species related to diet, spatial foraging behavior, sex or taxonomic classification and which specie is a better pest suppressor. Bats were captured by mist nets and stable isotope analysis of carbon and nitrogen (?13C e ?15N, respectively) were used to access its food source. Through the analysis of ?13C and ?15N of insects, we determined the proportion of plants with photosynthetic cycles of C3 and C4 in bats\' diet and its trophic level. It was captured 90 bats of 11 species, three families and four dietary categories, corresponding to 66% of the total local richness estimated. From those, five are insectivorous species. Molossus molossus were the most abundant specie, followed by Artibeus lituratus and Glossophaga soricina. Carbon values showed that insectivores, frugivores and nectarivores consume insects, including pests, in different proportions per specie and diet group. Besides, ?15N values showed that bat trophic level were very similar, so bats are more generalist than usually assumed. This study points a need to quantify this important ecosystem service provided by bats that can reduce diseases and crop damages